SURVEY DAN ANALISA BANGUNAN STMIK PALANGKA RAYA - Noor Hamidah; Maulida Maulida (Jurnal Teknika: Jurnal Teoritis dan Terapan Bidang Keteknikan, 2025)
Colleges function as learning centers that provide interactive academic environments. The Palangka Raya College of Informatics and Computer Management (STMIK) as the location of the research as a higher education institution located in Palangka Raya City, Central Kalimantan Province. The STMIK Palangka Raya building is designed to provide facilities that are in accordance with academic needs and accommodate teaching and learning activities for students, lecturers, and administrative staff focusing on informatics and computer management. The purpose of the study was to conduct a survey and analysis of the STMIK Palangka Raya building. The research method uses a qualitative method with a descriptive description of the results of the STMIK Palangka Raya building survey. STMIK Palangka Raya is designed with attention to the principles of security, accessibility, and user comfort. STMIK building materials used are of high quality and pay attention to energy efficiency. The research stages include analyzing the potential existence of STMIK, conducting visual observations and analyzing the availability of natural lighting in the STMIK building as an important factor because it affects the teaching and learning process related to the visual comfort of users of the space. Analysis of learning space as an analysis of the identification of campus building designs that provide student learning interest and analysis of green open spaces (parks) to create a beautiful learning environment and create fresh air. The output of the research is the identification of the location, structure, facilities, and lighting of STMIK Palangka Raya described in writing.